Students' Perspectives on TPACK-Enacted Pedagogy: A Quantitative Analysis of its Impact on Engagement and Learning Outcomes in a Tertiary EFL Classroom - Jawahar , Antony; Singh, Charanjit Kaur Swaran (International Journal of Language and Literary Studies, 2026)
Research on Technological Pedagogical Content Knowledge (TPACK) has predominantly focused on teachers' knowledge and practices, while the student perspective remains underexplored. This study addresses this gap by examining tertiary EFL students' perceptions of TPACK-enacted pedagogy and its relationship with academic engagement and self-reported learning outcomes. A quantitative cross-sectional survey design was employed with 187 undergraduate EFL students at a public university in Oman. Participants completed a 15-item Likert-scale questionnaire measuring three constructs: Student-Perceived TPACK Enactment, Student Engagement, and Self-Reported Learning Outcomes. Data were analyzed using descriptive statistics, Pearson correlation, regression, and bootstrapped mediation analysis. Results revealed strong positive correlations between perceived TPACK enactment and both student engagement (r = .790, p < .001) and learning outcomes (r = .792, p < .001). Regression analyses indicated perceived TPACK quality explained approximately 62% of variance in both outcome variables. Mediation analysis revealed that student engagement partially mediated the TPACK-learning outcomes relationship (indirect effect = 0.441, 95% BCa CI [.331, .551]), accounting for 53.1% of the total effect. These findings suggest that students' perceptions of effective technology integration are strongly associated with higher engagement and enhanced learning outcomes through both direct and engagement-mediated pathways. The study highlights the importance of incorporating student perspectives when evaluating technology integration effectiveness in EFL instruction.